Coastal protection through NbS in times of uncertainty. A case study of Bjärred, Sweden - Nohed,Anna (Master Thesis Series in Environmental Studies and Sustainability Science, 2023)
The global climate crisis presents significant social challenges and threatens biodiversity. Climate change is increasing the vulnerability of coastal areas, leading to more erosion and flooding. Nature-based solutions (NbS) offer a multifaceted approach to address these issues. This thesis examines the use of NbS for coastal protection in Bjärred, southern Sweden, and the municipality's strategies for planning, implementing, and monitoring sustainable solutions in the face of climate change uncertainties. Based on literature and stakeholder interviews, the analysis highlights NbS's suitability for mitigating coastal zone uncertainties. However, long-term effectiveness remains uncertain, necessitating further research and follow-up. To ensure that NbS can withstand more frequent storms and erosion, improved permit processes and enhanced community engagement in Bjärred and within the municipality are essential. This study underscores NbS's potential but emphasizes the importance of continuous evaluation and collaboration with residents for a resilient coastal future.
Keywords: Nbs; Coastal protection; Sustainability science; Bjärred; Uncertainty; Beach nourishment